Survivability of probiotic under simulated gastrointestinal conditions as affected by synbiotic (alginate-arabinoxylan) encapsulation - Nuaman, Muhammad; Afzaal, Muhammad; Saeed, Farhan; Ahmed, Aftab; Asghar, Aasma; Kamilah, Hanisah; Hussain, Shahzad; Ndagire, Catherine (Taylor and Francis, 2024)
The food industry is faced with a significant challenge in maintaining the viability and stability of probiotics during processing and in model food. Encapsulation technology offers a promising solution to this issue. This study was aimed to investigate the effect of Sodium Alginate (SA) and arabinoxylan (AX) composite encapsulation on the viability & stability of Lactobacillus rhamnosus GG. The AX was extracted from maize and characterized, and then the SA-AX composite was used to encapsulate the probiotics. The resulting microbeads were analyzed for their morphological, molecular, and physicochemical properties. The MAX-SA microbeads demonstrated the highest efficiency at 97.9 ± 0.6%, followed by MAX at 95 ± 1.5% and SA at 92 ± 1.4%. The FTIR spectra revealed specific functional groups in the samples. The MAX-SA and MSA matrices had a dispersed structure, while the MAX matrix had a smooth microstructure. The microcapsules had an average size ranging from 718 ± 2 mm to 734 ± 2 mm. The viability of the encapsulated probiotics was assessed under storage conditions, simulated gastrointestinal conditions, and model food. Encapsulated probiotics showed higher viability than free probiotics in simulated gastrointestinal conditions, and pineapple juice fortified with encapsulated probiotics showed a higher probiotic count. Overall, the study found that MAX-SA was the most effective in maintaining probiotic viability under stressed conditions.